Fast Determination of Manganese in Milk and Similar Infant Food Samples Using Multivariate Optimization and GF AAS. (13th October 2011) - de Amorim, Flávia Regina; Nascentes, Clésia Cristina; Franco, Milton Batista; da Silva, José Bento Borba
Abstract : Manganese is an essential element, but high levels in foods can be toxic mainly for children. A fast and efficient method to determine Mn in milk and other infant foods using slurries and liquid samples is presented. Slurries were prepared in ultrapure water with 10 minutes of sonication. Liquid samples were diluted in ultrapure water when necessary. Multivariate optimization was used to establish some optimal analytical parameters through a fractional factorial design and a central composite design. Slurred and diluted samples were analyzed directly by GF AAS. The method presented limit of detection of (0.98 ± 0.04 ) μ g L −1, characteristic mass of (2.9 ± 0.3 ) pg (recommended value 2 pg), RSD of 2.3% (n = 5 ), and linear range from 0.98 to 20.0 μ g L −1 using iridium as permanent modifier. The accuracy was evaluated analyzing two certified reference materials: nonfat milk powder (SRM1549) and whole milk powder (SRM8435). The powdered samples concentrations were between 0.210 and 26.3 μ g g −1 .